Using NSQIP to Investigate SCIP Deficiencies in Surgical Patients With a High Risk of Developing Hospital-Associated Urinary Tract Infections. (September 2014) - Trickey, Amber W.; Crosby, Moira E.; Vasaly, Fran; Donovan, Jean; Moynihan, John; Reines, H. David
The study objectives were to identify risk factors for surgical patients who develop postoperative urinary tract infections (UTIs) and to characterize urethral catheter practices at the study hospital. Patients from the 2006-2010 institutional National Surgical Quality Improvement Program database were evaluated. Patients with UTIs within 30 postoperative days (n = 116) were compared to patients without UTIs (n = 8685) using multivariable logistic regression. A nested case-control study evaluated the effects of catheter practices on postoperative UTI using conditional logistic regression. Independent predictors of UTI were sex, age, inpatient stay, functional status, renal failure, preoperative transfusion, and preoperative hospital stay. Compared with controls, patients with UTI more often maintained catheters for >2 postoperative days (66% vs 43%, P < .001) and had longer mean catheter duration (11.6 vs 5.1 days, P < .001). Study findings led to institutional recommendations to reduce catheter-associated UTIs. Quality improvement initiatives can increase awareness of performance enhancement opportunities and encourage collaborative, interdisciplinary improvement through shared objectives.